Influence of implantation ions on the electronic structure of GaP(111) surface - Donaev S.B., Umirzakov B.E., Abduvayitov A.A. (International Journal of Advanced Science and Technology, 2020)
In this article, the relationship between the band gap Eg and the sizes of nanocrystalline phases is studied. It has been established that in the case of surface sizes of phases d less than 35–40 nm (thickness 3.5–4 nm), quantum-size effects disappear in the Ga0.6Al0.4P nanocrystalline phases. The band gap of the Ga0.6Al0.4P nanocrystalline phases, depending on their size, increases from 2.4 eV (at d = 30-35 nm) to 3.1 eV (at d = 10-12 nm).